Integrated single-cell transcriptome analysis reveals heterogeneity of esophageal squamous cell carcinoma microenvironment - Dinh, Huy Q.; Pan, Feng; Wang, Geng; Huang, Qing-Feng; Olingy, Claire E.; Wu, Zhi-Yong; Wang, Shao-Hong; Xu, Xin; Xu, Xiu-E; He, Jian-Zhong; Yang, Qian; Orsulic, Sandra; et al. (Nature communications, 2021)
The tumor microenvironment is a highly complex ecosystem of diverse cell types, which shape cancer biology and impact the responsiveness to therapy. Here, we analyze the microenvironment of esophageal squamous cell carcinoma (ESCC) using single-cell transcriptome sequencing in 62,161 cells from blood, adjacent nonmalignant and matched tumor samples from 11 ESCC patients. We uncover heterogeneity in most cell types of the ESCC stroma, particularly in the fibroblast and immune cell compartments. We identify a tumor-specific subset of CST1 + myofibroblasts with prognostic values and potential biological significance. CST1 + myofibroblasts are also highly tumor-specific in other cancer types. Additionally, a subset of antigen-presenting fibroblasts is revealed and validated. Analyses of myeloid and T lymphoid lineages highlight the immunosuppressive nature of the ESCC microenvironment, and identify cancer-specific expression of immune checkpoint inhibitors. This work establishes a rich resource of stromal cell types of the ESCC microenvironment for further understanding of ESCC biology. The microenvironment of oesophageal squamous cell carcinomas (ESCC) is heterogeneous and can strongly impact response to treatment. Here, the authors characterize the ESCC tumour microenvironment with single-cell RNA-seq, finding CST1 + myofibroblasts with potential biological and prognostic significance as well as immunosuppression signatures.